Equipment regulation as a prevention measure for acute knee injuries in alpine ski racing - Kröll, J.; Spörri, J.; Gilgien, M.; Schwameder, H.; Müller, E. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Within the classification of severe injuries, the most frequently injured body part was the knee (62,3%),[1] with a rupture of the anterior cruciate ligament (ACL) as being the most frequent diagnosis.[2] The majority of knee injuries occurred while the skier was still skiing the course (83%).[3] The so-called self-steering effect of the ski, which enables athletes to perform turns with high amount of carving, favours a `catch of the edge` in the event of an out-of-balance situation. As a result, the athlete is unable to control the ski and the ski`s behaviour becomes unpredictable.[4] In such cases, the skis´ behaviour is perceived to be aggressive at the ski snow interaction, which has been suggested by expert stakeholders to represent one of the main contributors to typical mechanisms of knee injuries.[5] Consequently, efforts were made to (i) design, (ii) evaluate and (iii) finally implement equipment which reduces the risk of severe knee injuries: (i) By reducing the self-steering effect of the equipment, a reduction of the aggressiveness at the ski snow interaction was hypothesised, particularly in out-of-balance situations. Potential equipment interventions were ski sidecut radius and standing height of the athlete.[5] (ii) Across several independent field experiments the effect of different equipment interventions on relevant biomechanical variables were investigated. It was for instance experimentally shown, that skiing on skis with greater sidecut radius results in an increased ski turn radius and, therefore, provides evidence for reduced self-steering of the ski.[6] Another study depicted that skis with greater sidecut radius potentially reduce the kinetic variables related to, as well as the athletes` perception of, aggressive ski behaviour.[7] (iii) However, it was also shown that skis with a substantially greater sidecut radius might lead to a significant loss of attractiveness for spectators.[7] Therefore, potential benefits (injury prevention) and costs (attractiveness) have to be weighed against each other when implementing new specification on equipment within the International Ski Federation´s (FIS) competition rules. ABSTRACT FROM AUTHOR